Total Quality Management Practices and Performance of Manufacturing Firms in Uganda: Case of Metro Cement Ltd - Abdullah, Mohamed (Digital Repository of Theses, 2024)
The aim of this study is to investigate the relationship between total quality management (TQM) practices and the performance of manufacturing firms in Uganda, using Metro Cement Ltd as a case study. The study employs a mixed-methods research design, consisting of a survey and interviews with employees and management of Metro Cement Ltd. The survey is used to collect quantitative data on the TQM practices and performance of the company. The data is analyzed using descriptive statistics, correlation analysis, and regression analysis to identify the relationship between TQM practices and performance. The interviews are used to collect qualitative data on the perceptions and experiences of employees and management regarding TQM practices and their impact on the company's performance. The findings of the study show that TQM practices are positively related to the performance of Metro Cement Ltd. The study identifies several TQM practices that significantly influence the company's performance, including continuous improvement, employee involvement, customer focus, and leadership commitment. The study also reveals that the implementation of TQM practices has led to improvements in product quality, customer satisfaction, and employee morale. The study concludes that the adoption and implementation of TQM practices can improve the performance of manufacturing firms in Uganda, and recommends that other companies in the sector should adopt TQM practices to enhance their performance. The study also recommends that Metro Cement Ltd should continue to invest in TQM practices and identify areas for further improvement to maintain its competitive advantage in the market. Total Quality Management (TQM) is a management philosophy that emphasizes continuous improvement of all aspects of an organization, including its products, services, processes, and people. TQM is based on the belief that quality is everyone's responsibility and that it can be achieved through the involvement of all employees.